Badania marketingowe w procesie kształtowania wizerunku miasta w przestrzeni europejskiej - Perenc, Józef; Szeremet, Paweł; Wojtkiewicz, Monika (Marketing Research in the Process of the Creating of a City Image in the European Space, 2006)
Creating a positive image is one of the most important rules of professional marketing issues. The idea of creating the image is very essential on every level. A positive image developed over the years has become a part of successful municipality policy. It becomes even more important in the uniting Europe. One of the most important tools in creating an effective image is marketing research. Unfortunately it is hard to measure one's point of view because of very different ways of seeing the world, which have their basic foundations ensuing from culture differences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 223-231